An Integrated Analysis of miRNAs and Methylated Genes Encoding mRNAs and lncRNAs in Sheep Breeds with Different Fecundity - Miao, Xiangyang; Luo, Qingmiao; Zhao, Huijing; Qin, Xiaoyu (Frontiers in Physiology, 2017)
In our previous study, we investigated the regulatory relationship between lncRNAs, miRNA, and mRNAs in an effort to shed light onto the regulatory mechanisms involved in sheep fecundity. As an extension of this study, here, we aimed to identify potential regulators of sheep fecundity using a genome-wide analysis of miRNAs and the methylated genes encoding mRNAs and lncRNAs in the ovaries of Dorset sheep (low fecundity) and Small Tail Han ewes (high fecundity) with the genotype BB (Han BB) and the genotype ++ (Han ++) by performing RNA-Seq and MeDIP-Seq analyses. Methylated coding-non-coding gene co-expression networks for Han and Dorset sheep were constructed using the methylated genes encoding the differentially expressed mRNAs and lncRNAs identified in this study. In the Han BB vs. Dorset comparison, the lncRNAs TTC26 and MYH15 had the largest degree. Similarly, the lncRNA NYAP1 had the largest degree in the Han ++ vs. Dorset comparison. None of the methylated genes encoding lncRNAs were co-expressed with the methylated genes encoding mRNAs in the Han BB vs. Han ++ comparison. The methylated genes encoding lncRNAs identified here may play a vital regulatory role in sheep breeding. Our results suggest that miRNAs might play a key role in sheep prolificacy by regulating target genes related to thyroid hormone synthesis, and methylated genes encoding lncRNAs associated with tight junctions might contribute to the high breeding rate in Han sheep. These findings may contribute to a deeper understanding of sheep prolificacy.